ChemInform Abstract: Acceptorless Dehydrogenative Synthesis of 2‐Substituted Quinazolines from 2‐Aminobenzylamine with Primary Alcohols or Aldehydes by Heterogeneous Pt Catalysts. Issue 18 (May 2015) - Chaudhari, Chandan; Hakim Siddiki, S. M. A.; Tamura, Masazumi; Shimizu, Ken‐ichi
Abstract The ceria‐supported catalyst is recyclable and reusable at least 2 times.